(untitled) - Kramer, Sydelle (New York, 2004)
When Portuguese sailor Ferdinand Magellan set sail from Spain in 1519, he believed he could get to the Spice Islands by sailing west through or around the New World. He was right, but what he didn't know was that the treacherous voyage would take him three years and cost him his life. Black-and-white line drawings illustrate Magellan's life and voyage, with sidebars and a time line that enhance readers' understanding of the period.
Keywords: Explorers,Nhà thám hiểm; Biography,Tiểu sử; Portugal,Bồ Đào Nha